2011
DOI: 10.1074/jbc.m110.182618
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants in Streptococcal Unsaturated Glucuronyl Hydrolase for Recognition of Glycosaminoglycan Sulfate Groups

Abstract: Pathogenic Streptococcus agalactiae produces polysaccharide lyases and unsaturated glucuronyl hydrolase (UGL), which are prerequisite for complete degradation of mammalian extracellular matrices, including glycosaminoglycans such as chondroitin and hyaluronan. Unlike the Bacillus enzyme, streptococcal UGLs prefer sulfated glycosaminoglycans. Here, we show the loop flexibility for substrate binding and structural determinants for recognition of glycosaminoglycan sulfate groups in S. agalactiae UGL (SagUGL). UGL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
25
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Specific inhibitors of UGL are therefore expected to provide anti-bacterial drugs with no side effects. In addition, we demonstrated inducible mRNA expression of the streptococcal enzyme in the presence of GAG (16) and identified structural determinants of the preference of streptococcal UGL for sulfated substrates with 1,3-glycosidic bonds (12). However, the enzyme recognition mechanism for 1,4-glycosidic bond-type substrates from heparin and heparan sulfate remains unknown.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Specific inhibitors of UGL are therefore expected to provide anti-bacterial drugs with no side effects. In addition, we demonstrated inducible mRNA expression of the streptococcal enzyme in the presence of GAG (16) and identified structural determinants of the preference of streptococcal UGL for sulfated substrates with 1,3-glycosidic bonds (12). However, the enzyme recognition mechanism for 1,4-glycosidic bond-type substrates from heparin and heparan sulfate remains unknown.…”
mentioning
confidence: 97%
“…1B) (11). Carbon atoms C-3, C-4, C-5, and C-6 of unsaturated GlcUA (⌬GlcUA) and IdoUA (⌬IdoUA) are located in a single plane because of the formation of double bonds between C-4 and C-5 (12). Because GlcUA is a C-5 epimer of IdoUA, ⌬GlcUA and ⌬IdoUA are identical in structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, streptococcal UGL has been demonstrated to act on various unsaturated disaccharides, such as hyaluronan, chondroitin sulfate, heparin, and heparan sulfate, and to release unsaturated uronic acids and amino sugars (9,14). Due to the lack of the hydroxyl group at C4, unsaturated glucuronic (⌬GlcUA) and iduronic acids (⌬IdoUA) are chemically identical (Fig.…”
mentioning
confidence: 99%
“…We have identified unsaturated glucuronyl hydrolase (UGL), which is essential for degrading unsaturated disaccharides to constituent monosaccharides (i.e. unsaturated uronic acids and amino sugars) in bacteria, including streptococci (8,9), and found that a genome segment termed the UGL genetic cluster is responsible for the depolymerization, import, and degradation of glycosaminoglycans in streptococci, such as Streptococcus agalactiae, Streptococcus pneumoniae, and Streptococcus pyogenes (10) (see Fig. 2A).…”
mentioning
confidence: 99%